2016
DOI: 10.1016/j.jmii.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of codon usage preference in hemagglutinin genes of the swine-origin influenza A (H1N1) virus

Abstract: This study proposes a new and effective way to gain a better understanding of the features of the S-OIV genome and evolutionary processes based on the codon usage pattern. It is useful to trace influenza viral origins and cross-species virus transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Studies have shown that the higher the gene expression level is, the stronger is the preferred use of codon [1][2][3]6,15,16,49,[55][56][57][58][59][60]. In our study, the codon usage bias results of all cotton species were shown in S1 Table. The correlation between the parameters of 4 cotton species and 4 subgenomes had the same rule, except the correlation between G3s and C3s.…”
Section: Correlation Analysis Between Codon Usage Bias Indicesmentioning
confidence: 74%
See 1 more Smart Citation
“…Studies have shown that the higher the gene expression level is, the stronger is the preferred use of codon [1][2][3]6,15,16,49,[55][56][57][58][59][60]. In our study, the codon usage bias results of all cotton species were shown in S1 Table. The correlation between the parameters of 4 cotton species and 4 subgenomes had the same rule, except the correlation between G3s and C3s.…”
Section: Correlation Analysis Between Codon Usage Bias Indicesmentioning
confidence: 74%
“…The RSCU value is the ratio between the actual observed values of the codon and the theoretical expectations. It reflects the relative usage preference for the specific composition of codons encoding the same amino acid [49]. If RSCU = 1, codon usage is unbiased; if RSCU > 1, specific codon frequency is higher than other synonymous codons, otherwise, the frequency is low [49].…”
Section: Enc-plot (Enc Versus Gc3smentioning
confidence: 99%
“…Influenza HA is a highly glycosylated protein [32][33][34]. Cellular lectin receptors may recognize the glycans on HA of influenza A virus, allowing for the binding of the virus to the cells and permitting internalization.…”
Section: Introductionmentioning
confidence: 99%
“…The relative synonymous codon usage (RSCU) value which is measured by the ratio between the actual observed values of the codon and the theoretical expectations was also calculated. RSCU reflects the relative usage preference for the specific codons encoding the same amino acid [92]. If RSCU value equals to 1, codon usage is supposed to be unbiased but if RSCU>1, specific codon frequency is higher than other synonymous codons and codon usage is considered to be biased [93].…”
Section: Methodsmentioning
confidence: 99%